Angiopoietin 2 expression in the cornea and its control of corneal neovascularisation. Issue 7 (4th May 2016) - Ferrari, Giulio; Giacomini, Chiara; Bignami, Fabio; Moi, Davide; Ranghetti, Anna; Doglioni, Claudio; Naldini, Luigi; Rama, Paolo; Mazzieri, Roberta
Abstract : Purpose: To define proangiogenic angiopoietin 2 (ANG2) expression and role(s) in human and mouse vascularised corneas. Further, to evaluate the effect of ANG2 inhibition on corneal neovascularisation (CNV). Methods: CNV was induced in FVB mice by means of intrastromal suture placement. One group of animals was sacrificed 10 days later; corneas were immunostained for ANG2 and compared with (i) mouse non-vascularised corneas and (ii) human vascularised and non-vascularised corneas. A second group of CNV animals was treated systemically with an anti-ANG2 antibody. After 10 days, the corneas were whole-mounted, stained for CD31 and LYVE1 and lymphatic/blood vessels quantified. In another set of experiments, the corneal basal Bowman membrane was either (i) removed or (ii) left in place. After 2 or 10 days the corneas were removed and immunostained for collagen IV, ANG2, CD31, LYVE1, CD11b and MRC1 markers. Results: In human beings and mice, ANG2 is expressed only in the epithelium, and, mildly, in the endothelium, of the avascular cornea. Instead, it is expressed in the epithelium, endothelium and stroma of vascularised corneas. Disruption of the Bowman membrane is associated with a significant increase of (i) ANG2 stromal expression and (ii) proangiogenic macrophage infiltration in the corneal stroma. Finally, blocking ANG2 significantly reduced hemangiogenesis, lymphangiogenesis and macrophage infiltration. Conclusions: Balancing proper healing and good vision is crucial in the cornea, constantly exposed to potential injuries. In this paper, we suggest the existence of a mechanism regulating the onset of inflammation (and associated CNV) depending on injury severity.